Effects of Transition Strip on Aerodynamic Yaw Derivatives of MULDICON Wing using an Oscillating Rig at Various Angle of Attack - Haider, Bilal; Mansor, Shuhaimi; Mat, Shabudin; Wan Omar, Wan Zaidi; Nasir, Nazri (International Journal of Aviation Science and Engineering - AVIA, 2024)
This paper presents the effects of the passive flow control technique using transition strips on the transient aerodynamic stability derivative measured on the MULDICON AVT251 wing. The experiments were performed at two configurations; clean wing configuration and the transition strips attached to wing leading edge. MULDICON wind tunnel model was designed and fabricated in UTM based on the AVT251 design. The dynamic measurements were carried out in the Universiti Teknologi Malaysia Aerolab wind tunnel for Reynolds number of 0.3x106 & 0.475x106. MULDICON model was confined to oscillate with a single degree of freedom in yawing motion. The aerodynamic stability derivatives &  are measured as aerodynamic stiffness and damping by extracting the stiffness and damping of the dynamic oscillating rig system. Springs of different stiffness are used to vary the oscillation frequencies with the reduced frequency range of 0.004-0.08. The unsteady aerodynamics effects are examined for both wing configurations. The angle of attack varies from α = 0° to 20° by comparing the transient measurements from the dynamic UTM-LST to the steady-state wind tunnel measurements. The dynamic results indicate that the aerodynamic stiffness derivative is not constant and exceeds the static values and strongly correlates with reduced frequency. The aerodynamic damping derivative is a function of reduced frequency as the damping derivatives become more negative with the increase of the reduced frequency. The amplification factor for the stiffness derivative is above unity which indicates that the steady-state derivative is under-predicted.